The creative disjunctures of twenty-first century global storytelling: Rana Dasgupta's Tokyo Cancelled. Issue 1 (2nd January 2020) - Eng Hun Lee, Jason
ABSTRACT: This essay argues that Tokyo Cancelled (2005) paradoxically seeks to resist the very forms of world-making totality implied in its narration by rendering the world simultaneously as knowable and unfathomable, flat and uneven. Featuring an ensemble of narratives that are locally-grounded yet part of a wider global network, Tokyo Cancelled activates a series of creative disjunctures via its decentred narrative structure and use of irrealist storytelling techniques. Through its frame narrative, the simulated orality of its thirteen anonymous storytellers resist a master narrative of globality by creating an ambivalent, deterritorialised reading of place, while the novel's irrealist aesthetic serves a double function of depicting the non-objective, disorganised nature of a globalised world, whilst also pointing to the very real issues of global inequality through its asymmetrical portrayal of the economic world-system. As the individual narratives feature marginalised subjects, I explore ways in which Tokyo Cancelled highlights conditions of displacement, empowerment and alienation within a deeply fractured neoliberal economy, and in doing so, how the novel presents one successful example of experimental writing in twenty-first-century works of global fiction by opening up a borderland site for its protagonists to connect in the world-city.